Strategi Guru SKI Dalam Mengatasi Keterbatasan Sumber Belajar Untuk Meningkatkan Pemahaman Belajar Siswa Di MIS Al Washliyah Desa Bangun Sari Baru Tanjung Morawa Deli Serdang - Khairunnisa, Dwi; Nasution , Hasnil Aida; Hidayah , Nurul (Journal of Innovative and Creativity, 2026)
This research aims to describe the strategies implemented by Islamic Cultural History (SKI) teachers at MIS Al Washliyah, Bangun Sari Baru Village, in overcoming the challenges of limited learning resources. In many rural educational settings, the scarcity of textbooks and instructional media often hinders the achievement of comprehensive student understanding. This study employs a qualitative descriptive approach, with data collection techniques including in-depth interviews, participatory observation, and documentation. The findings reveal that teachers navigate these constraints through a "Teacher as a Living Resource" strategy, which involves contextual storytelling, the independent use of personal mobile technology to present digital historical artifacts, and the implementation of peer tutoring to maximize shared textbooks. These adaptive strategies have proven effective in transforming a passive learning environment into an interactive one, significantly enhancing student engagement and conceptual understanding. The study concludes that teacher pedagogical resilience and creativity are the primary determinants of educational success when physical infrastructure is lacking.